Upaya Meningkatkan Profesionalisme Guru Melalui Supervisi Klinis dengan Pendekatan Lesson Study - Ahmad Hidayat (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2021)
The background of the research is the low motivation of teachers in planning learning at the target madrasah. The research objective is to improve teacher professionalism through clinical supervision with a lesson study approach. The sample taken in this action research was 20 people, consisting of 6 teachers from MTs Legokjawa and 14 teachers from MTs Negeri 2 Pangandaran. The research was conducted using the School Action Research (PTS) method. The research was carried out in two cycles, each cycle consisting of four stages, namely planning, implementation, reflection and evaluation. The action taken is a simulation of teaching peer tutors using a Learning Implementation Plan (RPP) with a Lesson Study approach. The results showed that the average value of the teaching simulation results in cycle 1 was 66.68 and increased to 80.42 in cycle 2. The attitude of participants to the PBM simulation in cycle 1 was 76.69 and increased to 83.35 in cycle 2. The average value of lesson plans in cycle 1 was 73.35 and 82.37 in cycle 2. The average value of PBM in cycle 1 was 74.72 and 84.97 in cycle 2. The results of the study concluded that academic supervision by means of clinical supervision with an approach Lesson study fosters teacher motivation to excel in order to improve professionalism.